Geographic Information Systems Web-Based Application Mapping Health - Oktaviani F; Susanty W (International Conference on Engineering and Technology Development (ICETD), 2017)
Health is one of the basic human needs besides food, shelter and education, because only in a healthy condition people can live, grow and work better (Agoes & Jacob, 1996). Humans are instrumental in maintaining and improving the health of themselves and the environment. Hence, humans have knowledge regarding the effort to avoid and how to cure a type of disease to undergo treatment at a community health service centers. To go to the center of public health services often come across some obstacles such as the lack of geographical information of the community health service centers. As the development of technology that is growing rapidly, geographic information system is still manual is also being developed into a better form is a Geographic Information System Technology (Geographic Information System) and currently has known the terms Desktop GIS, Web GIS etc. Web GIS the basic concept is a system designed to work with data references spatial or geographical coordinates. GIS has the ability to perform data processing and perform certain operations by displaying and analyzing data. Resume This paper discusses the Web GIS, methods or tools used as well as the resulting output. Based on the description above, the writer gives the title "Web-Based GeographicInformation System for Health Mapping Applications"